2021
DOI: 10.1021/acs.joc.1c01902
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced 6π-Electrocyclization of a 1,3,5-Hexatriene System Containing an Allomaltol Fragment

Abstract: For the first time, the possibility of photocyclization of the 1,3,5-hexatriene system containing a fragment of allomaltol was demonstrated. A preparative method for the synthesis of previously unknown benzo­[5,6]­chromeno­[8,7-d]­oxazole-2,7­(3H)-diones was developed based on the investigated photoreaction. A distinctive feature of this approach is the modification of the starting terarylenes aimed at blocking the competitive process leading to side reactions of the pyranone fragment. It was shown that the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…Initially, based on the previously obtained results for terarylenes with an oxazolone bridge fragment, we chose pyrazole 16 containing a methoxy group in the allomaltol core as a model object for studying photochemical properties. As it was shown previously for similar oxazolone derivatives [ 26 ] the presence of a methoxyl substituent in the compound 16 must exclude the occurrence of ESIPT-promoted photoprocesses. Therefore, it could be expected that UV irradiation of such a compound would lead only to 6π-electrocyclization of the 1,3,5-hexatriene system.…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations
“…Initially, based on the previously obtained results for terarylenes with an oxazolone bridge fragment, we chose pyrazole 16 containing a methoxy group in the allomaltol core as a model object for studying photochemical properties. As it was shown previously for similar oxazolone derivatives [ 26 ] the presence of a methoxyl substituent in the compound 16 must exclude the occurrence of ESIPT-promoted photoprocesses. Therefore, it could be expected that UV irradiation of such a compound would lead only to 6π-electrocyclization of the 1,3,5-hexatriene system.…”
Section: Resultsmentioning
confidence: 65%
“…As it was demonstrated earlier [ 26 ], UV irradiation of terarylenes containing oxazolone and 3-hydroxypyran-4-one fragments 9 can lead to two types of photoprocesses. Based on the aforementioned results we can assume that the key difference of the related pyrazole derivatives considered in this report is the absence of a pathway associated with 6π-electrocyclization.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…Komogortsev et al 87 reported an unusual method for the synthesis of 1,3,5-hexatrienes 228 with an allomaltol fragment via the condensation of 1,2-diketones 227 with aldehydes and NH 4 OAc in acetic acid. Solutions of 228 in Petri dishes were exposed to UV radiation at 365 nm (Vilber Lourmat VL-6.LM lamp) for 30 h, which resulted in the formation of photoproducts 229 .…”
Section: Miscellaneousmentioning
confidence: 99%